WTO Membership and the Shift to Consumption Taxes - Thiess Buettner; Boryana Madzharova (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using a panel of 97 mostly developing and transitional countries for the period 1990-2011, this paper explores fiscal implications of membership in the World Trade Organization (WTO). Em-ploying robust difference-in-difference specifications as well as semi-parametric methods, we find that countries joining the WTO experience a decline in revenues from import duties between 0.5% and 1% of GDP. Revenue losses from import duties are more than compensated for by an increase in consumption taxes. Although triggered by WTO accession, the shift towards consumption taxes, in particular to VAT, typically takes place before trade liberalization commitments result in declining tariff revenues.
Keywords: H20; F13; 330; trade liberalization; tax reform; value added tax; GATT; WTO; anticipation effects; synthetic control group method